Development of Technology Adoption Framework on the use of Smart Classrooms - Sangalang , Nino (Gyan Management Journal, 2023)
Smart classrooms have emerged as an innovative solution for educational institutions to deliver quality education during the COVID-19 pandemic. The study focuses on students’ perspectives and preferences regarding smart classrooms and recommends effective implementation strategies based on educators’ experiences and a well-established Technology Adoption Framework (TAF). The study employed a mixed-methods approach, combining quantitative and qualitative research methods. 188 students who experienced learning in a smart classroom participated in the survey based on the Technology Acceptance Model (TAM), and 16 experienced teachers who taught in smart classrooms participated in qualitative research based on SWOT and PESTLE analyses. Based on the researcher’s analysis, it has been found that students are highly interested in having a smart classroom in their educational institution. The study highlights students’ receptiveness and sheds light on the valuable insights shared by teachers regarding the optimum utilization of smart technology in the classroom environment. The researcher has developed a Technology Adoption Framework named SMARTCLASS, which includes several crucial components such as communication, training, management support, and user involvement. This framework is expected to enhance the classroom’s overall teaching and learning experience, ensuring optimal technology and resource utilization.